(untitled) (International Journal of Engineering and Computer Science, 2017)
SDN (Software Defined Network) is a new networking approach towards current networking industry. S.D.N has attracted the researchers attention, because there is wide scope of innovation and research. The main concept behind the SDN networks is the separation of controller from data plane. This natural feature makes SDN adaptive of being flexible and scalable. We are mentioning some of the important components those are needed to make current SDN networks even better and efficient that can be managed easily and updated whenever needed, without any interruption of services. Also we have discussed how we can manage the data plane, control plane and how we can identify where fault has occurred